Limb-Girdle Muscular Dystrophies (LGMDs): The Clinical Application of NGS Analysis, a Family Case Report - Strafella, Claudia; Campoli, Giulia; Galota, Rosaria Maria; Caputo, Valerio; Pagliaroli, Giulia; Carboni, Stefania; Zampatti, Stefania; Peconi, Cristina; Mela, Julia; Sancricca, Cristina; Primiano, Guido; Minozzi, Giulietta; et al. (Frontiers in Neurology, 2019)
The diagnosis of LGMD2A (calpainopathy) can be challenging due to genetic heterogeneity and to high similarity with other LGMDs or neuromuscular disorders. In this setting, NGS panels are highly recommended to perform differential diagnosis, identify new causative mutations and enable genotype-phenotype correlations. In this manuscript, the case of a patient affected by LGMD2A is reported, for which the application of a defined custom designed NGS panel allowed to confirm the diagnosis of calpainopathy linked with two heterozygous variants in CAPN3, namely c.550delA and c.1813G>C. The first variant has been extensively described in relation to calpainopathy. The second variant c.1813G>C, instead, is novel and has been predicted to be probably damaging. In addition, NGS analysis on the proband revealed a heterozygous variant (c.550C>T) in the LMNA gene, which is associated with dilated cardiomyopathy. The variant is novel and has been predicted to be deleterious by subsequent bioinformatic analysis. Successively, segregation analysis was performed on family members. Interestingly, none of them showed neuromuscular symptoms but the mother was diagnosed with bradycardia and syncopal episodes and showed a positive family history for cardiomyopathy. The segregation analysis reported that the proband inherited the c.1813G>C (CAPN3) from the father who was a healthy carrier. The mother was positive for c.550delA (CAPN3) and c.550C>T (LMNA), suggesting thereby a possible genetic explanation for her cardiovascular problems. Segregation analysis, therefore, confirmed the inheritance pattern of the variants carried by the proband and highlighted a familiarity for cardiomyopathy which should not be neglected. The NGS analysis was further performed on the partner of the proband, to estimate the reproductive risk of the couple. The partner was negative to NGS screening, suggesting thereby a low risk to have an affected child with calpainopathy and 50% probability to inherit the LMNA variant. This case report showed the clinical utility of the NGS panel in providing accurate LGMD2A diagnosis and identifying complex phenotypes originating from mutations in multiple genes. However, NGS results should always be accomplished by a dedicated genetic counseling, not only to evaluate the recurrence and reproductive risks but also to uncover unexpected findings which can be clinically significant.